SOME ASPECTS OF THE IMPLEMENTATION OF THE MAIN FUNCTIONS OF PUBLIC COUNCILS - Matusova, Olena (Public Management and Policy, 2026)
The article is devoted to the study of the main functions of public councils. The author analyzes various approaches to the separation of functions and proves that the main functions of public councils are control, consultation and expert. The article draws attention to the fact that the concept of “public monitoring” proposed at the regulatory level does not reflect the essence of the relevant activities of public councils, since it is focused on systematic and continuous observation, collection and assessment of information, but does not cover inspections, detection of violations, and active intervention in correcting the situation. The position is argued according to which public monitoring should be defined as the first stage of public control. Attention is drawn to the fact that public councils, by their essential purpose, perform the function of public control and a proposal is made to harmonize the relevant legal norms. The author also studies the consultative function of public councils and emphasizes that public councils are and should remain important subjects of public-state dialogue. This approach is based on the thesis that the institution of public consultations allows citizens to directly express their opinion in the public and legal sphere. The article emphasizes that the development of information and communication technologies significantly activates the exchange of opinions, information, and constructive debates. The author also draws attention to the threat of excluding public councils from the process of conducting public consultations on the basis of prospective legislation and suggests ways to overcome it. Special attention is paid to the role of public councils in conducting public expertise, which is a form of implementing the constitutional rights of citizens to participate in the management of state affairs. It is argued that public expertise should be based on professional knowledge and a clear methodology. In order to optimize the rules for conducting public expertise, it is worth determining the indicators of the effectiveness of its procedures. Based on the research conducted, the paper substantiates the conclusion that the development of specific forms of implementing the function of public control, advisory and expert functions requires further scientific research and the implementation of the experience of best European practices.